Prioritizing Customer Loyalty Strategies Using Customer Journey Mapping and Analytic Hierarchy Process - Ihsananda, Nadhim; Safirin, Moch Tutuk; Syaifullah, Hafid (Universitas Muhammadiyah Sidoarjo, 2025)
Background (General): The rapid growth of Indonesia’s culinary sector has intensified competition, making customer loyalty a key determinant of business sustainability and competitiveness. Background (Specific): Small and medium enterprises (SMEs), such as Jatinangor House, face challenges in maintaining loyalty due to inconsistent marketing strategies, limited resources, and underutilization of digital platforms. Knowledge Gap: While Customer Journey Mapping (CJM) and Analytic Hierarchy Process (AHP) have been studied individually, their integrated application in the Indonesian SME food sector to analyze and prioritize loyalty strategies remains underexplored. Aims: This study investigates the dominant strategy for enhancing customer loyalty at Jatinangor House Ketintang Branch by combining CJM to identify experiential gaps and AHP to prioritize strategic interventions. Results: Findings reveal that standardization of service, portion size, and cleanliness is the most critical priority (weight 0.365), followed by improvement of online menu information and digital promotion, whereas loyalty programs are less effective without operational consistency. Novelty: The study uniquely integrates CJM and AHP to provide structured, customer-centric marketing strategies for SMEs in the Indonesian food industry. Implications: These results emphasize that improving fundamental service quality and digital visibility must precede loyalty initiatives, offering both practical recommendations for SME management and theoretical contributions to marketing strategy research Highlights: Integration of CJM and AHP reveals service quality as the top loyalty driver. Digital visibility and menu information are crucial for customer consideration. Loyalty programs are ineffective without operational consistency. Keywords: Customer Journey Mapping, Analytic Hierarchy Process, Customer Loyalty, Marketing Strategy, SMEs